2022
DOI: 10.1111/iju.14913
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for predicting survival of renal cell carcinoma with tumor thrombus based on perioperative clinicopathological factors from a Chinese high‐volume center

Abstract: Objectives: To investigate perioperative clinicopathological predictors and establish a predictive nomogram for survival in patients with renal cell carcinoma and venous tumor thrombus undergoing nephrectomy and thrombectomy. Methods: Patients with renal cell carcinoma and venous tumor thrombus undergoing nephrectomy and thrombectomy were included in the study between January 2014 and June 2020. Cox regression analysis was used for univariate and multivariate survival analyses. A predictive nomogram for surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A growing body of research reported the value of nomogram that has been widely used in clinical oncology, with intuitive graphs simplifying the use of prediction models ( 21 , 22 ). But it was absent in the nomogram for LRRC.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research reported the value of nomogram that has been widely used in clinical oncology, with intuitive graphs simplifying the use of prediction models ( 21 , 22 ). But it was absent in the nomogram for LRRC.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Li et al . developed a unique nomogram to promote the risk stratification of overall survival in patients with RCC with IVC thrombus following surgery using a Chinese cohort comprising 228 patients in a retrospective study 3 . The nomogram comprised five factors: hemoglobin levels, sarcomatoid component, perirenal fat invasion, histopathology, and metastasis at surgery.…”
mentioning
confidence: 99%
“…Li et al . developed a predictive nomogram for survival in patients with renal cell carcinoma (RCC) and inferior vena cava (IVC) tumor thrombus, which can greatly promote risk stratification and planning 1 . This nomogram will be a useful tool in clinical practice for postoperative follow‐up and adjuvant treatment options for RCC with IVC thrombus.…”
mentioning
confidence: 99%